2005
DOI: 10.1109/jmems.2005.856653
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nanoscale heating on electrical transport in RF MEMS switch contacts

Abstract: Abstract-This paper explores contact heating in microelectromechanical systems (MEMS) switches with contact spot sizes less than 100 nm in diameter. Experiments are conducted to demonstrate that contact heating causes a drop in contact resistance. However, existing theory is shown to over-predict heating for MEMS switch contacts because it does not consider ballistic transport of electrons in the contact. Therefore, we extend the theory and develop a predictive model that shows excellent agreement with the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
83
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 38 publications
5
83
0
Order By: Relevance
“…• C to 100 • C [2], [3]. The authors who reported the lower temperature did not rule out thermal breakdown of bonds between the gold and an adsorbed film layer as the mechanism producing decreased resistance at 65…”
Section: Contact Theorymentioning
confidence: 98%
See 2 more Smart Citations
“…• C to 100 • C [2], [3]. The authors who reported the lower temperature did not rule out thermal breakdown of bonds between the gold and an adsorbed film layer as the mechanism producing decreased resistance at 65…”
Section: Contact Theorymentioning
confidence: 98%
“…• C [2]. An accurate representation of the surface roughness is needed to generate meaningful predictions for contact area and resistance.…”
Section: Contact Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The current is constricted when passing through small asperities, heating in contact is extremely localized on the asperity proximity [16]. Another concern in the work is to investigate the thermoelectrical behavior of electrical contacts.…”
Section: Introductionmentioning
confidence: 99%
“…An analytical expression for voltage-temperature (V-T) relation was given by Holm [8], in which the maximum temperature depended only on the total voltage of a long constriction; while for the small spots, size on the order of mean free path, the expression of Holm was invalid [4]. Jensen et al then considered the ballistic effect, and introduced an improved model for small spots [16].…”
Section: Introductionmentioning
confidence: 99%